2015
DOI: 10.13109/zptm.2015.61.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Lebensqualität oder Lebenserwartung? Kriterien und Informationsquellen für die Entscheidungsfindung bei Patienten im Vorfeld von Aortenklappenoperationen/ Quality of life or life expectancy? Criteria and sources of information in the decision-making of patients undergoing aortic valve surgery

Abstract: Preoperative counseling by a physician plays an essential role in the decision-making process prior to cardiac surgery. Patients want to be involved in decision-making, though they do not want to bear the full responsibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In the case of heart valve surgery, studies show that there is not only the question regarding the type of procedure, but also the choice between biological and mechanical valve; too little knowledge and ability to assess information were seen as causes for difficulties in weighing up a decision [ 37 , 38 ]. Additionally, the peer-group exchange of information and individual experiences concerning, e.g., comorbidities or therapy side-effects, is perceived as helpful (which is in contrast to the findings of Schmied et al (2015), that social support or peers were sources to which little recourse was made) [ 39 ]. Its promotion may indirectly contribute to the development of individual HL, especially in the context of existing comorbidities (since there is evidence that comorbidities among patients with implantable cardioverter defibrillators and pacemakers are associated with inadequate HL [ 40 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of heart valve surgery, studies show that there is not only the question regarding the type of procedure, but also the choice between biological and mechanical valve; too little knowledge and ability to assess information were seen as causes for difficulties in weighing up a decision [ 37 , 38 ]. Additionally, the peer-group exchange of information and individual experiences concerning, e.g., comorbidities or therapy side-effects, is perceived as helpful (which is in contrast to the findings of Schmied et al (2015), that social support or peers were sources to which little recourse was made) [ 39 ]. Its promotion may indirectly contribute to the development of individual HL, especially in the context of existing comorbidities (since there is evidence that comorbidities among patients with implantable cardioverter defibrillators and pacemakers are associated with inadequate HL [ 40 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this aspect, other findings suggested that participants did not want to be part of the direct decision but rather, in general, be emotionally supported by friends [ 37 , 58 ]. Then again, some studies showed that health professionals were valued in the decision-making process as “co-deciders” who take part in the decision or even take it from the patient [ 39 , 53 , 59 ]. Astin et al (2017) recommend to explore patients’ beliefs and preferences concerning quality and quantity of life in consultations [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the abstract missed inclusion details then the method paper of the study was screened. Inclusion criteria were studies that had (1) assessed the QoL of older adults, (2) had a minimum of one population group of people with epilepsy aged 60 and older, (3) and used at least one standardised QoL measure (either specific to epilepsy or general). The types of study designs included for review were randomised controlled trials (RCT), cohort, cross-sectional, observational and case reports.…”
Section: Study Selectionmentioning
confidence: 99%
“…1 ), step three – information about treatment options, was most widely described and mentioned within twelve studies. Ten studies reported the means by which information was delivered (decision aid [ 27 , 33 , 34 ] or through HCP [ 28 , 29 , 32 , 36 , 37 , 39 , 41 ]) while two studies did not make any clear specifications [ 31 , 40 ]. A second most widely applied SDM step was the exploration of patient wishes and concerns in the decision-making process (step 4)[ 27 , 29 , 32 34 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%